An easy way to distinguish DNA from protein: an experiment for general chemistry. - López Valentín, Dulce María; Pulido Cordoba, Liliana; Chávez Reyes, Arturo (2012)
We propose a classroom experiment to complement a classroom activity described by Ellis et al. in this Journal. In the Ellis activity students extracted long polymer fibers from the cells of common foods. In this experiment, the identity of the long polymer fibers as either DNA or protein can be determined by doing three accessible, inexpensive, and easy tests. Two of the tests, temperature and the acid-medium effect, are based on the physicochemical properties of DNA (reversible denaturalization), and the third test is a qualitative determination of proteins (absent in DNA). The results of these three tests provide evidence to distinguish the isolated molecule of DNA from proteins that might look like DNA.